Syariah: Dinamic Legal System - Sadzali, Munawir (Al-Jami'ah Research Centre, 1987)
First of all I would like to thanks my great friend, His excellency Mr. H. Mohamed, the Minister Transport and the Minister in Charge of the Muslim Religious and Culture Affaire of the Republic of Sri Lanka. For his kind invitation to me to take part in this very important Islamic gathering, the Third Asian Forum of the international Shariah Conference; and I deem it an exceptional privilege and honour to be invited to address this forum, attended by prominent Islamic jurists and scholar, all with in international repute, I am doubtful trough, that I Shall be able to come up to the expectation, and to satisfy the intellectual curiosity of this professionally well infromed audience.